The Role of Motor Activity in the Social Integration of Disabled Individuals - Yevhen Imas; Olha Borysova; Iryna Kohut (Lesya Ukrainka Volyn National University, 2017)
The current relevance of the research. Over a significant period of human development disabled people were considered to be dependent and were regarded as weak, incapable, etc. Frequently, dependence, a result of disability, was exaggerated by teachers, family members and society. Adaptive physical culture and sportscan reduce dependence and social isolation, helping disabled people to become full members of society. Methods of the reseacrh: analysis and generalization of special, scientific and methodical literature, the Internet; standardized documents; comparative method, abstracting, logical and theoretical analysis. The results of the study. The main goal of lessons of adaptive physical culture and sports is to increase the level of social integration, welfare, reduction of the isolation of disabled people by changing public opinion about disability and their psychological attitude to themselves. To achieve this goal, first of all, it is necessary to reduce the level of discrimination which is associated with disability. Secondly, to encourage and stimulate disabled people to realize their own potential and, thirdly, to implement changes in society that promote the full social implementation of this category of people.At the same time, the competitions in adaptive sports, first was regarded as local, have turned into the widespread international sports events for athletes with different forms of disability. The success of the modern Deaflympics, Paralympic Games and World Games of Special Olympics is both a testimony and a factor in changing the attitude of society towards disability. Disabled people are not a burden or an issue of social expenditure, but they are assets of a society that can make a significant contribution to its development and prosperity. It is necessary to create appropriate conditions, eliminating physical and social barriers. Training sessions and competitions contribute to it in terms of creating a barrier-free environment, and changing public attitudes. Conclusions. Motor activity training of disabled people, their participation in competitions, can not only improve their physical, mental, leadership and other qualities, promote the development of communicative abilities, self-confidence, confidence in their own abilities, but also provide the preconditions for maximum full-fledged social integration of disabled people, as well as the humanization of public relations in general.